2022
DOI: 10.3389/fnbeh.2022.836996
|View full text |Cite
|
Sign up to set email alerts
|

Friend of the Devil: Negative Social Influences Driving Substance Use Disorders

Abstract: Substance use disorders in humans have significant social influences, both positive and negative. While prosocial behaviors promote group cooperation and are naturally rewarding, distressing social encounters, such as aggression exhibited by a conspecific, are aversive and can enhance the sensitivity to rewarding substances, promote the acquisition of drug-taking, and reinstate drug-seeking. On the other hand, withdrawal and prolonged abstinence from drugs of abuse can promote social avoidance and suppress soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 226 publications
(287 reference statements)
1
13
0
Order By: Relevance
“…In addition, traumas experienced in childhood (physical or emotional abuse, neglect), even occurring only once [43,44], lead to adverse physiological consequences and poor health outcomes, causing, for example, increased cortisol levels that subsequently increase the risk of substance use [42]. This could explain the relationship between the mechanisms involved in coping with trauma and those that lead to substance use, putting stress at the center of the relationship: while milder forms can result in positive behavioral effects, severe or chronic levels can cripple it, so that the individual will try to cope with it by taking substances that can quell perceived stress and anxiety, increasing the likelihood of developing an addiction [44].…”
Section: Childhoodmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, traumas experienced in childhood (physical or emotional abuse, neglect), even occurring only once [43,44], lead to adverse physiological consequences and poor health outcomes, causing, for example, increased cortisol levels that subsequently increase the risk of substance use [42]. This could explain the relationship between the mechanisms involved in coping with trauma and those that lead to substance use, putting stress at the center of the relationship: while milder forms can result in positive behavioral effects, severe or chronic levels can cripple it, so that the individual will try to cope with it by taking substances that can quell perceived stress and anxiety, increasing the likelihood of developing an addiction [44].…”
Section: Childhoodmentioning
confidence: 99%
“…As widely known, adolescence is a crucial period for biological, psychological, and social development, but it is also a sensitive time when one is particularly susceptible to substance use, its negative effects, and subsequent addictions [44,45]. Early encounters with substances increase the likelihood of future problems (physical, behavioral, social, and health) but also raise the risk of addiction if you start before age 18 [44].…”
Section: Adolescencementioning
confidence: 99%
See 2 more Smart Citations
“…Inhibiting these inhibitory neurons leads to a disinhibition of the dopaminergic neurons which project into the nucleus accumbens causing an increase in dopamine transmission [47,107]. Generally, in opioid models of rodents, opioid receptor agonists are observed to cause social aversion [108] some studies suggesting this effect is regulated by noradrenaline and serotonin signaling [109,110]. However, Piccin and Contarino observed that withdrawal from chronic morphine exposure in adult mice increased social approach [111].…”
Section: 4potential Mechanismsmentioning
confidence: 99%